(untitled) (American Journal of Pedagogical and Educational Research, 2025)
The article examines a contemporary criteria-based methodology and diagnostic instruments for assessing and developing communicative competence in prospective teachers. Through tools such as structured pedagogical imitation, communicative stress-testing, digital discourse analysis, and personal trajectory portfolios, the linguistic, pragmatic, intercultural, and strategic layers of competence are precisely measured and purposefully developed. This approach ensures transparency, objectivity, and a developmental orientation in assessment.